From High-Risk Behaviors to Problem-Solving Strategies: Acceptance and Commitment Therapy Effects on Addiction Susceptible Adolescents in Cyberspace - Zandkarimi, Ghazal; Tagva, Ebrahimi (Journal of Child and Adolescent Psychiatry, 2021)
This study aimed to evaluate acceptance and commitment therapy (ACT) effectiveness in reducing high-risk behaviors and elevating problem-solving strategies in adolescents with addiction susceptibility in cyberspace. This study is longitudinal with quantitative methods of data collection and analysis. The target community in this research was 60 female students randomly selected from a Persian high school in Iran. Participants were randomly divided and placed equally into the experimental and control groups. The participants’ entry criteria were gender, aged from 15 to 18 years, addiction susceptibility, and high-risk behaviors cut-off points. Eight training sessions of ACT were presented in cyberspace for the experimental group between the pre-test and post-test intervals. Data collection instruments were the Iranian youth risk-taking scale, problem-solving strategies, and Iranian adolescents’ addiction susceptibility questionnaires. Participants were followed up after two months. The results using multivariate analysis of among subjects ANOVA showed ACT significantly influenced high-risk behaviors and its’ sub-scales except for the violence (p < .001).Furthermore, ACT affected the problem-solving strategies and its’ sub-scales instead of control, creativity, and confidence (p < .001). According to the findings, ACT decreased high-risk behaviors such as drug abuse, smoking, and unprotected sexual behaviors. These changes might be due to decreased helplessness and avoidance as well as increased acceptance and tendency to solve problems. Instead, problem-solving strategies were improved through ACT cyber treatment.
Keywords: Acceptance and commitment therapy; addiction susceptibility; cyber training; high-risk behaviors; problem-solving strategies